Study about the healthcare sustainable strategies: Analysing collaborations for improved patient outcomes and operational efficiency - Nazir, Shafquat; Dayanandan, Ramya (Edelweiss Applied Science and Technology, 2025)
This paper studies the critical success and sustainability factors influencing the success of strategic healthcare partnerships. A mixed-methods approach was used to collect data from 200 widely representative cross-sections of healthcare stakeholders, including providers, administrators, IT experts, and community-based personnel. A strong positive relationship was found between shared goals, technological integration, effective communication, resource mobilization, and partnership outcomes, all of which were quantitatively related to one another. Challenging issues related to resource allocation, interoperability, best practices for mission alignment, and structured communication were also highlighted through qualitative insights. Important objectives must be aligned, innovative technology must be adopted, resources must be managed collaboratively, and sustainability management must be planned. The contribution of this research to the healthcare field includes practical recommendations for healthcare leaders on how to achieve better partnership effectiveness to improve patient outcomes and operational efficiency. Overall, the study’s contribution is valuable in advancing resilient, adaptive healthcare collaborations.